Religion, Spirituality and Speech-Language Pathology: A Viewpoint for Ensuring Patient-Centred Holistic Care - Mathisen, Bernice (Journal of religion and health, 2015)
This paper presents a viewpoint concerning the largely neglected clinical relevance of spirituality and religious belief in speech-language pathology (SLP) assessments, interventions and outcomes across the lifespan. An overview of the refereed SLP literature is presented with regard to religion and spirituality. It was found that while there is increasing research with regard to spirituality, health and well-being, there is very little specific to SLP. What is available and clinically relevant, generally relates to holistic care and/or cultural and linguistic diversity. Amidst the health care literature, however, there is a growing number of recommended instruments (for religious/spiritual screening) sensitive to intercultural and interfaith issues that are currently available to medical, nursing, allied health and chaplaincy practitioners. These instruments can also be of value to SLPs to ensure holistic assessments and interventions. It would seem timely for SLPs (and other allied health practitioners) to consider including spiritual screenings/assessments as part of their clinical practice so as to ensure appropriate holistic care. This would also mean undertaking research and including relevant education within tertiary institutions and professional development programs.